Kemanjuran Teknik Motivational Interviewing Untuk Meningkatkan Motivasi Belajar Siswa SMK - Indra Ratna Dewi; Siti Sutarmi Fadhilah; Agus Tri Susilo (Universitas Sebelas Maret, 2022)
Abstract: This study aims to test the effectiveness of the Motivational Interviewing technique to increase the learning motivation of SMK students. This study uses a Non-equivalent Control Group Design. The research subjects of each experimental and control group were seven students selected using the purposive sampling technique. Research data were collected using a learning motivation scale. The results of the Mann-Whitney test analysis showed a p-value score of 0.002 (0.002 <0.05). It can be concluded that there is a significant difference in the posttest score of learning motivation between the experimental group and the control group. This difference occurred because of the treatment for the experimental group in the form of motivational interviewing techniques..Abstrak: Penelitian ini bertujuan untuk menguji keefektifan teknik Motivational Interviewing untuk meningkatkan motivasi belajar siswa SMK. Penelitian ini menggunakan Non equivalent Control Group Design. Subjek penelitian masing-masing kelompok eksperimen dan kelompok kontrol berjumlah tujuh siswa yang dipilih menggunakan teknik purposive sampling. Data penelitian dikumpulkan menggunakan skala motivasi belajar. Hasil analisis Uji Mann-Whitney menunjukkan skor p-value 0,002 (0,002<0,05). Dapat disimpulkan bahwa ada perbedaan yang signifikan dari skor hasil posttest motivasi belajar antara kelompok eksperimen dengan kelompok kontrol. Perbedaan tersebut terjadi karena adanya treatment untuk kelompok eksperimen berupa teknik motivational interviewing.